Enantioselective nickel-catalyzed arylative intramolecular allylations of allenyl electrophiles - NGUYEN, THI LE NHON (2020)
Catalytic enantioselective conjugate additions of organometallic reagents to electron-deficient alkenes and asymmetric allylation of carbonyl compounds are important reactions for the construction of new carbon-carbon bonds. However, a method using an allylnickel species to perform catalytic nucleophilic allylation enantioselectively remains considerably underdeveloped and only a handful of examples have been described. In this thesis, enantioselective nickel-catalyzed arylative and alkenylative intramolecular allylations of allenyl electrophiles with boronic acids are described.